2019
DOI: 10.1080/01612840.2019.1565872
|View full text |Cite
|
Sign up to set email alerts
|

Attention, Externalizing, and Internalizing Problems of Youth Exposed to Parental Incarceration

Abstract: Introduction: Few studies have examined the effects of parental incarceration (PI) on outcomes above and beyond other risk and adverse childhood experiences (ACEs). Aim: To examine 1) the associations between PI and mental health problems (attention, externalizing, internalizing, and total behavioral problems) and 2) the mediating role of current socioeconomic status and cumulative ACEs. Method: An observational and cross-sectional design was employed. Analyses included hierarchical multivariable linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Eight studies were found related to this category. One of these eight studies addressed both paternal and maternal incarceration separately [ 53 ], two of them paternal incarceration [ 15 , 54 ], one maternal incarceration [ 55 ], and the last three did not discriminate the gender of the parent in prison [ 56 , 57 , 58 , 59 ]. The vast majority of these investigations only included variables related to academic performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were found related to this category. One of these eight studies addressed both paternal and maternal incarceration separately [ 53 ], two of them paternal incarceration [ 15 , 54 ], one maternal incarceration [ 55 ], and the last three did not discriminate the gender of the parent in prison [ 56 , 57 , 58 , 59 ]. The vast majority of these investigations only included variables related to academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, children and adolescents have shown greater difficulties in their physical [ 5 ], cognitive [ 6 ] and socioemotional development [ 7 , 8 , 9 ], as well as in their school life [ 10 ], living conditions [ 11 ], and a greater number of psychosocial risks (e.g., substance abuse [ 12 ], delinquency [ 13 ], and violent behavior [ 9 ]). However, some studies have not found a relationship between parental incarceration and some of these variables, e.g., [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some countries may not report their racial or ethnically disproportionate incarceration, these patterns exist in many countries worldwide. 3 Studies show that when children are exposed to the criminal justice system-either through witnessing the arrest of their parent or attending court proceedings-they are traumatized by the experience (Boch et al, 2019;Turney & Goodsell, 2018). Not only is it potentially traumatic for children to visit their incarcerated family members, they fear for their parents' safety as well (Aiello & McCorkel, 2018;Fasah, 2018).…”
Section: Making Children the Prioritymentioning
confidence: 99%
“…I do not want to give short shrift to the contributions of many other authors to Volume 40, whose papers were not part of a "special issue." Among the thought-provoking and valuable articles published in 2019 were papers on men with an eating disorder (Lyons, McAndrew, & Warne, 2019); victims of narcissistic abuse (Howard, 2019); problems of youth whose parents are incarcerated (Boch, Warren, & Ford, 2019); mental health needs of refugee women (Felsman, Humphreys, & Kronk, 2019); and refugee children (Cleary, West, Foong, McLean, & Kornhaber, 2019). A welcome trend this year is an increase in the number of letters to the editor, a healthy indicator of reader engagement and desire to respond.…”
Section: From the Editormentioning
confidence: 99%